Comparative assessment of the signs of instability of atherosclerotic plaques in the carotid arteries in elderly patients with acute coronary syndrome with duplex scanning and computed tomography angiography - E. V. Konstantinova; A. A. Sagatelyan; A. A. Bogdanova; E. S. Pershina; V. S. Shemenkova; A. V. Svet; A. A. Oganesyan; M. Yu. Gilyarov (Кардиоваскулярная терапия и профилактика)
Aim. To study the signs of instability of atherosclerotic plaques (ASP) in the carotid arteries in elderly patients with acute coronary syndrome (ACS) in the comparative aspect of duplex ultrasound scanning (DUS) and computed tomography angiography (CT).Material and methods. 27 patients with ACS (75 years and over) were included in the study. The signs of instability of ASP were assessed according to DUS and CT.Results. The signs of instability of ASP according to DUS were detected in 85,7%, according to CT — in 84,6%. The following signs were detected with DUS and CT: the presence of irregular plaque surface including signs of ulceration — 6,4 and 11,6% (p=0,021), positive remodeling — 3,8 and 3,8% (p=0,998), signs of local calcification — 23 and 25,9% (p=0,536), heterogenous structure — 55,1 and 46,8% (p=0,045), hypoechogenic component and low-density areas — 11,5 and 11,6% (p= 0,998). The correlation analysis showed high comparability of DUS and CT: irregular plaque surface with ulceration (K=0,624, p=0,02), positive remodeling (K=1, p<0,001), calcification (K=0,858, p<0,001), heterogenous structure (K=0,754, p<0,001), the presence of hypoechogenic component and low-density areas (K=1, p<0,001).Conclusion. The study of elderly patients with ACS found high comparability of DUS and CT in the definition of the signs of instability of ASP in the carotid arteries. It is possible to use DUS as a routine method for assessing carotid atherosclerosis in patients of this group, which can reduce the risk of complications during CT, shorten the examination time, and minimize economic costs.